The Moral Ambiguity of Public Prosecution - Mendlow, Gabriel S. (2021)
Classic crimes like theft and assault are in the first instance wrongs against individuals, not against the state or the polity that it represents. Yet our legal system denies crime victims the right to initiate or intervene in the criminal process, relegating them to the roles of witness or bystander—even as the system treats prosecution as an institutional analog of the interpersonal processes of moral blame and accountability, which give pride of place to those most directly wronged. Public prosecution reigns supreme, with the state claiming primary and exclusive moral standing to call offenders to account for their wrongs. Although likely justified all things considered, this legal arrangement upends the structures of accountability familiar from ordinary life, where the victims of wrongdoing enjoy moral standing of a caliber greater than that of most if not all third parties. By inverting these structures of accountability, the state that acts as exclusive public prosecutor exceeds its moral standing and incurs a debt to the crime victim, who retains a persisting moral complaint, even against a state that justifiably monopolizes the prosecution function. The victim’s persisting moral complaint is different from the well known grievance that a criminal legal system that marginalizes or excludes crime victims risks injuring their dignity and impairing their prospects for vindication and reconciliation. If the state showed crime victims greater solicitude and accommodated their interests and considered preferences more deliberately, the criminal process might dignify victims and enhance their wellbeing. But the state still would exceed its moral standing if it accommodated the victim as a matter of benevolent grace, rather than in recognition of the victim’s moral prerogative